The View from Augusta: Developments Growing Out of the Speaker’s 2013 Round Table Discussions and 2014 Aging Summit - Eves, Mark; Maurer, Jessica (Maine Policy Review, 2015)
Mark Eves and Jessica Maurer describe the significant progress made in Maine since 2013 in addressing aging-related issues through collaboration between legislative and community-based efforts. The Maine Aging Initiative, formed in 2014 and coordinated through the Maine Council on Aging and the House Speaker’s office, plays a significant role in supporting these efforts.
Keywords: aging; Maine; Maine Aging Initiative; aging-related legislation